Pertanggungjawaban Hukum Terhadap Pelaku Tindak Pidana Penganiayaan - Sahril Fadillah; Heni Siswanto; Fristia Berdian Tamza; Ahmad Irzal Fardiansyah; Maya Shafira (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Assault is an intentional act that causes pain or injury to another person's body. So it can be interpreted that abuse is a form of criminal act. Based on the explanation of Article 351 paragraph (1) of the Criminal Code, it is emphasized that abuse that causes the victim to suffer serious injuries is carried out by a person against another person, even against objects, even though a person must be responsible for his actions. Criminal responsibility is intended to determine whether a suspect/defendant is responsible for a crime that occurred or not. What are the inhibiting factors in criminal liability for perpetrators of abuse which resulted in serious injuries to two victims based on Decision Number: 659/Pid.B/2019/PN.Tjk and what is criminal liability for perpetrators of criminal acts of abuse which resulted in serious injuries to two victims? Data analysis uses qualitative data analysis. The inhibiting factors in criminal accountability for perpetrators of abuse which resulted in serious injuries to two victims based on Decision Number: 659/Pid.B/2019/PN.Tjk are the legal factors themselves, law enforcement factors, means and facilities factors, community factors and cultural factors , community factors and law enforcement officers. Criminal liability for the perpetrator of the criminal act of abuse which resulted in serious injuries to two victims in Decision Number: 659/Pid.B/2019/PN.Tjk has met the value of criminal liability in accordance with the provisions of the actus because the defendant has committed an act that is prohibited as stated in it. in the Criminal Code.